2-Phenylnaphthalenes and a polyoxygenated cyclohexene from the stem and root extracts of Uvaria cherrevensis (Annonaceae) - Chiramet Auranwiwat (2018)
© 2017 Three new 2-phenylnaphthalene derivatives, cherrevenaphthalenes A–C (1–3), and a new polyoxygenated cyclohexene derivative, (−)-uvaribonol F (4) together with six known compounds, 5–10, were isolated from the stem and root extracts of Uvaria cherrevensis (Annonaceae). The structures of all isolated compounds were elucidated by spectroscopic analysis. The structures of 3 and 4 were further confirmed by single crystal X-ray diffraction methods. Compound 2 exhibited modest antiplasmodial activity against the P. falciparum stains TM4/8.2 and K1CB1 with IC50values of 18.8 ± 3.63 and 23.4 ± 4.08 μM, respectively, and weak cytotoxicity to a Vero cell line. Furthermore, compound 4 displayed cytotoxic activity against a KB cell line with an IC50value of 22.1 ± 0.42 μM but was non-cytotoxic to the Vero cell line. Compound 5 revealed stronger cytotoxicity towards the KB cell line, with an IC50value of 5.05 ± 0.86 μM and was nearly equally cytotoxic to the Vero cell line.